HUBUNGAN ANTARA STATUS GIZI TB/U DENGAN KEMAMPUAN KOGNITIF, FISIK, DAN SOSIO-EMOSIONAL ANAK USIA PRA-SEKOLAH Association of Height-For-Age Nutritional Status with Cognitive, Physical, and Socio-Emotional Ability of Pre-School Children - Vidya Anggarini Rahmasari; Lailatul Muniroh (Universitas Airlangga, 2021)
Pre-school period is one of the most important times for children’s growth and development. If there is a growth and development disturbance at this time, it will impact when the child is growing up. One of the factors which related with growth of pre-school children is nutritional status of height for age. The purpose of the study was to analyzed the relationship between the nutritional status of height for age with the cognitive, physical, and socio-emotional abilities of pre-school age children. This research was an analytical observational study using a cross sectional design. Sample of this study was 35 pre-school children selected randomly using simple random sampling. Samples were student of TK Hang Tuah 22, Candi, Sidoarjo. Data collection instrument includes the questionnaire on the characteristics of the subject and the respondent, a Denver instrument Developmental Screening Test II (DDST/Denver II). Spearman Rho test was used to analyze the data. The results showed that there was a relationship between height for age nutritional status with cognitive abilities. However, there was no relationship between the nutritional status of height for age with physical and socio-emotional ability. The conclusion of the study is nutritional status of height for age has a significant association with cognitive abilities in pre-school children. Thus, parents need to monitor the nutritional status height for age of their children by measure the anthropometric result periodically and fulfill the nutritional needs of protein, calcium, vitamin D, zinc, and others. Therefore, if there is any problem founded, it can be handled properly and will not aﬀect the growth and development of the children.